Neuroprotective effect of quercetin against radiation‐induced endoplasmic reticulum stress in neurons - Chatterjee, Jit; Langhnoja, Jaldeep; Pillai, Prakash P; Mustak, Mohammed S (Journal of biochemical and molecular toxicology, 2019)
The endoplasmic reticulum (ER) plays an important role in the regulation and maintenance of cellular homeostasis. However, unresolved ER stress leads to deleterious effects by inducing the accumulation of unfolded proteins in the cell. Here we have demonstrated the protective aspects of quercetin against radiation‐induced ER stress and against inflammation in primary cultured dorsal root ganglion (DRG) neurons. The mature DRG neurons were pretreated with different concentrations of quercetin (5‐100 μM) for 24 hours before 2 Gy gamma radiation exposure and then subjected to a cytotoxicity assay, quantitative real‐time polymerase chain reaction and Western blot analysis. The results showed that quercetin decreased the expression of BiP and C/EBP‐homologous protein, the ER stress marker genes along with downregulation of tumor necrosis factor‐α, JNK in irradiated DRG neurons. Furthermore, quercetin pretreatment significantly increased the cytoskeletal protein Tuj1 and the neurotrophin brain‐derived neurotrophic factor in the neuron. These results indicate that quercetin plays a neuroprotective role against radiation‐mediated ER stress and inflammatory responses.